Att predika för barn - några marginalanteckningar (Preaching to Children. Some Remarks from an Educational Point of View) - Hartman, Sven G. (Svenskt gudstjänstliv, 1989)
This paper contains some comments on Ellverson’s and Carlquist’s article Preaching for children. My main point is that it is not possible to say anything about how to preach to children if you don’t consider three questions first: a. Why should you preach to children? - Which are the educational goals for the sermon? b. To whom does the preacher speak - what is the preacher’s view on childhood and children, what knowledge do we have about children? c. What subject-matter should be chosen for the sermon? Preaching to children is considered as a rather bad educational method, especially if the goals are not defined by the preacher. In my research I have found that children's prerequisites for thinking and discussing philosophical and theological matters are often underestimated by grown-ups. The selection of subject- matter is problematic, since the Christian tradition contains several subjects that could be difficult or even harmful for children, not so much intellectually as mentally.